Turbin Angin menggunakan Pipa PVC sebagai Pembangkit Tenaga Listrik dan Pengusir Hama Burung Pipit - Yaman; Said Aiyub2; Subhan3; Taufik4; Nuraini5 (Jurnal Serambi Engineering, 2024)
The paddy fields are generally large expanses of land that are free of wind barriers, away from human settlements and power sources. Sparrows are one of the most common pests, which usually attack paddyfield in clusters. The researchers who use electronic equipment as controllers to produce output, sounds and electronic drives, use a power source from batteries. The wind turbine is one method of repelling sparrows and producing electricity, as the driving force for the sound-producing mechanical equipment, and the Nema17 motor as the generator for charging the battery. Paddy is grown seasonally so the wind turbine can be disassembled for use and for storage. Measurement of wind speed to determine blade length, with the help of Win & Wet website, blade design, power relationship characteristics with windspeed and turbine rotation were created. The blade length of 60 cm can produce the power of 40 W, with using a pulley belt timing ratio of 1: 3 can increase the dc direct voltage, the lowest is 4.23 volts at a wind speed of 1.08 m / s and the highest voltage is 14.97 volts at a wind speed of 3.4 m/s, can be utilised for charging 3.7 volt Li ion batteries.